Malaysian herbal-based entrepreneur intention to implement green practices - Sumin, Viduriati (2014)
The need for policies to foster green practices and sustainable environmental management involving consumers, organisations and business enterprises have been recognised as a priority world-wide. Various factors causing environmental degradation such as global warming, pollution, climate change, deforestation and the increasingly threatened biodiversity have triggered awareness among the upstream and downstream players in the industry, providing impetus particularly to herbalbased industries to practise sustainable and environmentally friendly management. Additionally, consumers are now increasingly concerned about environmental degradation and subsequently demand products produced under sustainable and environmentally friendly surroundings. This has not only placed pressure on entrepreneurs to move towards green practices, but also resulted in increasing the demand and supply for herbal-based products. However, in Malaysia, there are only a few companies that have obtained specific environmental management system certification such as MS 14001 and most of them are large companies with strong financial backing. The main difficulties for SMEs to comply with green practice include obtaining the equipment, resources and expertise in the related field. The green purchasing concept as well is still new in Malaysia and consumers are still not aware of the benefits of green practices yet. This is resulted in low participation in green management practices by small companies as compared with larger ones in Malaysia. Therefore, it is very difficult for SME entrepreneur to see a clear connection between the implementation of the environment management system (EMS) and its benefits. Empirical research On the effects of best practices of environmental management which enable firms to simultaneously protect the environment and reduce costs has been neglected. Thus in this study, the Theory of Planned Behaviour (TPB), and the perceived innovation characteristics in Diffusion of Innovation (DOl) theory are used to investigate the determinant factors of the herbal-based entrepreneurs' intentions to adopt green practices. Originally, the Perceived Innovation Characteristics were divided into five main elements; relative advantage, complexity, compatibility, triability and observability. However, the majority of empirical studies examining perceived relative advantage, complexity and compatibility represents the perceived of innovation characteristics in 001 theory. This study highlighted the elements of relative advantage and complexity since both can be loaded into the same variable. The objective of the study is to examine the perceptions and intentions of herbalbased entrepreneurs to adopt green practices using data collected from two hundred and fifty six (256) herbal-based entrepreneurs registered under the National Pharmaceuticals Bureau Control of Malaysia. Descriptive analysis, factor analysis and the structural equation model were applied to analyze the data. The structural equation modeling technique was used to evaluate the causal model and pooled confirmatory factor analysis was performed to examine the reliability and validity of the measurement model. The findings indicate that attitude, subjective norms and perceived behavioural control have positive effects on the intention to adopt green practices. However, the mediation effect test also reveals the statistically significant indirect relationship between the perceived innovation characteristics (perceived relative advantage and complexity) and intention to adopt green practices. This indicates the role of attitude as mediator between perceived relative advantage, complexity and intention. To achieve the final objective in the study, the moderation effect of company characteristics on the overall exogenous and endogenous constructs were tested. It was found that GMP and Halal logo certification obtained by entrepreneurs significantly moderate most of the exogenous construct paths and the intention to adopt green practices. Additionally, global networking moderates the relationship between the overall exogenous construct and the intention to go green. Results also show that imported raw herbs sources serve as the main moderator of the relationship between complexity - attitude, attitude - intention, perceived behavioral control - intention to adopt the green practices in the future. The findings of this study contribute to the literature by providing new empirical evidence on the applicability of the extended Theory of Planned Behavior. In terms of practical implications, the findings enable the govemment, stakeholders and policy makers to set a relevant benchmark for green practices in the herbal-based industries in Malaysia. Moreover, indicate that positive attitudes towards sustainability are being embraced by those who are concemed about the environment and the intention to adopt innovative green practices is realized by their possession of the caring attribute towards the environment.